2008
DOI: 10.1007/s00114-008-0495-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive disturbance of Japanese bumblebees by the introduced European bumblebee Bombus terrestris

Abstract: The European bumblebee, Bombus terrestris, is an invasive eusocial species whose distribution is expanding greatly beyond its native range because numerous colonies are imported to or locally produced in non-native countries for pollination of agricultural crops. Closely related species exist in Japan where the unrestricted import and use of B. terrestris has resulted in the establishment of wild colonies. Laboratory studies previously showed that B. terrestris and Japanese native species can copulate and prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 39 publications
0
45
0
4
Order By: Relevance
“…Therefore, most crossing between introduced B. terrestris and indigenous Japanese bumblebees would not lead to diploid worker production, and any resulting colonies should collapse without production of any reproductives. As previously mentioned, Kondo et al (2009) B. terrestris and indigenous B. ignitus, B. h. hypocrita, and B. h.…”
Section: Post-zygotic Isolationmentioning
confidence: 64%
See 2 more Smart Citations
“…Therefore, most crossing between introduced B. terrestris and indigenous Japanese bumblebees would not lead to diploid worker production, and any resulting colonies should collapse without production of any reproductives. As previously mentioned, Kondo et al (2009) B. terrestris and indigenous B. ignitus, B. h. hypocrita, and B. h.…”
Section: Post-zygotic Isolationmentioning
confidence: 64%
“…This finding suggests that (1) bumblebees discriminate conspecific mating partners via male sex pheromones, and (2) the species discrimination ability of virgin gynes and males is disrupted at close range. Kondo et al (2009) (Ono, personal communication). Bombus terrestris, B. ignitus, and B. hypocrita are phylogenetically closely related (Kawakita et al, 2004;Cameron et al, 2007).…”
Section: Pre-mating Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, analysis of the DNA sequences of the spermatozoa stored in the spermathecae of native queens in Hokkaido Island and Tohoku district showed that about 30% of B. hypocrita queens had mated with B. terrestris males. Given that a Bombus queen generally mates only once in her life, these high frequencies of interspecific mating with B. terrestris pose serious threats to the populations of native bumblebees in Japan (Kondo et al, 2009;see Tsuchida et al, 2010, this issue).…”
Section: Reproductive Disturbance By Interspecies Crossesmentioning
confidence: 99%
“…Invasions of B. terrestris in Japan are particularly important when considering the impact on native ecosystems because native bumblebee species and bumblebee-pollinated plants are abundant. Indeed, ecological impacts of B. terrestris on native bumblebee populations and bumblebee-pollinated plants have been reported within invaded regions of Japan (e.g., Dohzono et al, 2008;Inoue et al, 2008;Kondo et al, 2008). Investigations on the current invasion status of B. terrestris and its relationships with environmental factors are needed to provide primary information for the evaluation of potential future ecological risks.…”
Section: Introductionmentioning
confidence: 99%